Vasculogenic Potency of Bone Marrow- and Adipose Tissue-Derived Mesenchymal Stem/Stromal Cells Results in Differing Vascular Network Phenotypes in a Microfluidic Chip - Mykuliak, Anastasiia; Yrjänäinen, Alma; Mäki, Antti-Juhana; Gebraad, Arjen; Lampela, Ella; Kääriäinen, Minna; Pakarinen, Toni-Karri; Kallio, Pasi; Miettinen, Susanna; Vuorenpää, Hanna (Frontiers in Bioengineering and Biotechnology, 2022)
The vasculature is an essential, physiological element in virtually all human tissues. Formation of perfusable vasculature is therefore crucial for reliable tissue modeling. Three-dimensional vascular networks can be formed through the co-culture of endothelial cells (ECs) with stromal cells embedded in hydrogel. Mesenchymal stem/stromal cells (MSCs) derived from bone marrow (BMSCs) and adipose tissue (ASCs) are an attractive choice as stromal cells due to their natural perivascular localization and ability to support formation of mature and stable microvessels in vitro. So far, BMSCs and ASCs have been compared as vasculature-supporting cells in static cultures. In this study, BMSCs and ASCs were co-cultured with endothelial cells in a fibrin hydrogel in a perfusable microfluidic chip. We demonstrated that using MSCs of different origin resulted in vascular networks with distinct phenotypes. Both types of MSCs supported formation of mature and interconnected microvascular networks-on-a-chip. However, BMSCs induced formation of fully perfusable microvasculature with larger vessel area and length whereas ASCs resulted in partially perfusable microvascular networks. Immunostainings revealed that BMSCs outperformed ASCs in pericytic characteristics. Moreover, co-culture with BMSCs resulted in significantly higher expression levels of endothelial and pericyte-specific genes, as well as genes involved in vasculature maturation. Overall, our study provides valuable knowledge on the properties of MSCs as vasculature-supporting cells and highlights the importance of choosing the application-specific stromal cell source for vascularized organotypic models.